IMPLEMENTASI AKUNTABILITAS TERHADAP PENGELOLAAN ANGGARAN DI DEWAN PERWAKILAN RAKYAT KABUPATEN ACEH BARAT - Nila Trisna; Nodi Marefanda (Jurnal Public Policy, 2017)
The  purpose  of  this  research  is  to  know  and  to  explain  about  the  implementation  of accountability  for  the  management  of  the  budget  in  the  House  of  Representatives  District (DPRK)  Aceh  Barat.  This  research  uses  nomative  juridical method  and  nomative  empirical. Research specifications are descriptive analytical mind. The data source that is used secondary data, through investigations books, official documents and research results of the experts in the form of reports. In addition to the collection of legal materials, also collected primary data that is  done  with  how  to  perform  the  interview.  The  results  of  the  study  showed  that  the DPRK budget  is  a  part  that  is  not  an  inseparable  part  of  the  qanun  Regency  of  Aceh  Barat  about APBK.  The  study  also  follows  the  discussion  of  the  budget  of  other  SKPK  mechanism  and discussed together between a team of Local Government Budget and Budget Committee DPRK. The  realization  of  the  Secretariat  budget DPRK West Aceh  good  enough,  almost  all  planned activities  in 2016 can be  implemented. DPRK budget  supervision of West Aceh done by many parties, which is in addition to direct the Secretary of the DPRK authorities in West Aceh itself, also  done  by  Inspektorat  Jenderal, BPK  district  representatives  of  the  province  of Aceh  and BPKP Aceh Province. It is recommended that the preparation of the Secretariat budget DPRK West Aceh on the future can be more is clarified again to prevent overlapping budget spending to one activity will be but with a different name.  Keywords: Accountability, Budget Management and Planning